THE USE OF TiO2/ZEOLITE TO REDUCE THE CONCENTRATION OF NITRATE, NITRITE, AMMONIAC, PHOSPHATE, BOD, COD AND pH IN AGRICULTURAL WASTE WATER PHOTOLYSIS - Zilfa Zilfa; Rahmayeni Rahmayeni; Diana Vanda Wellia; Yulizar Yusuf; Putri Julanda Ardica; Siti Zahara; Muhammad Hafiz Reza (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2022)
This study aims to determine the effect of the use of TiO2/Zeolite on reducing concentrations of nitrate, nitrite, ammonia, phosphate, BOD, COD and pH in agricultural wastewater by photolysis. In this study, sample analysis was carried out using UV-Vis spectrophotometer and FTIR and for the characterization of TiO2/Zeolite catalysts using FTIR, XRD and SEM. In agricultural wastewater samples, the initial concentration of nitrate was 11,409 mg/L, nitrite was 0,424 mg/L, ammonia was 5,075 mg/L and phosphate was 5,364 mg/L. The most optimum decrease in concentration for nitrate, nitrite, ammonia and phosphate, respectively, was 4,332 mg/L with an irradiation time of 90 minutes; 0,118 mg/L with an irradiation time of 75 minutes; 0.395 mg/L with an irradiation time of 90 minutes and 1,207 mg/L with an irradiation time of 60 minutes on the addition of TiO2/Zeolite as much as 0.8 grams for the determination of nitrate and phosphate while for nitrite and ammonia as much as 0.6 grams. Prior to the degradation, the BOD value was 62,4 mg/L and the COD value was 107,07 mg/L. Meanwhile, after degradation, the BOD value decreased to 5,92 mg/L and COD to 35 mg/L. The results of the analysis using FTIR on agricultural wastewater show that there is no significant shift in wave number before and after degradation. The characterization of TiO2/Zeolite catalyst using FTIR, XRD and SEM did not show significant changes before and after the degradation process was carried out which indicated that TiO2/zeolite could be applied in degrading agricultural wastewater.